A COMMUNITY-BASED STUDY OF AGGRESSIVE-BEHAVIOR IN DEMENTIA - Ware, C; Fairburn, C; Hope, R (1990)
Aggressive behaviour is a serious care problem for families looking after patients with dementia. The aim of this study was to investigate, in a community sample of patients with dementia, the nature of aggressive behaviour and the settings in which it occurred. Thirty-seven subjects known to be aggressive were studied. The results show that the acts of aggression can be usefully classified on the basis of the circumstances in which they occur. It is argued that such a classification is likely to be of more value in understanding aetiology than is a classification based on the nature of the acts themselves.